2022
DOI: 10.3390/nano12091458
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High Surface Area—Group 13—Metal Oxides via Atomic Layer Deposition on Mesoporous Silica

Abstract: The atomic layer deposition of gallium and indium oxide was investigated on mesoporous silica powder and compared to the related aluminum oxide process. The respective oxide (GaOx, InOx) was deposited using sequential dosing of trimethylgallium or trimethylindium and water at 150 °C. In-situ thermogravimetry provided direct insight into the growth rates and deposition behavior. The highly amorphous and well-dispersed nature of the oxides was shown by XRD and STEM EDX-mappings. N2 sorption analysis revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 107 publications
0
20
0
Order By: Relevance
“…Therefore, the ratio between the exposed indium sites and total indium was higher on the IWI sample, which might be caused by the lower loading (8 wt % vs. 14 wt % In). It was previously shown that a monolayer of In 2 O 3 is formed after the second ALD cycle [56]. Hence, some indium atoms are already located in the sublayer after two ALD cycles.…”
Section: Co 2 Hydrogenation Activity Of the Ald Catalystsmentioning
confidence: 92%
See 3 more Smart Citations
“…Therefore, the ratio between the exposed indium sites and total indium was higher on the IWI sample, which might be caused by the lower loading (8 wt % vs. 14 wt % In). It was previously shown that a monolayer of In 2 O 3 is formed after the second ALD cycle [56]. Hence, some indium atoms are already located in the sublayer after two ALD cycles.…”
Section: Co 2 Hydrogenation Activity Of the Ald Catalystsmentioning
confidence: 92%
“…In this study, ALD experiments were carried out in a selfdesigned setup of which a detailed description is given elsewhere [55]. Trimethylindium (TMI) and water were used as precursor-reactant combination and the overall ALD process investigation is described in detail in [56]. Initially, the ALD growth behavior was validated by in situ thermogravimetric studies in a magnetic suspension balance (SI Fig.…”
Section: Atomic Layer Deposition Of Ino X On Zromentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a lot of methods have been developed to prepare atomically thin oxide films. Solution-phase synthesis can be applied simply in the commercial production of oxide films. , Magnetron sputtering and other vapor deposition methods could prepare uniformly distributed oxides. However, the thickness of the metal oxide films fabricated by solution-phase synthesis is uncontrollable, and the oxide films using physical methods are generally polycrystalline, which can result in unstable electrical properties due to grain boundaries, thus leading to unstable electronic properties. Hereby, finding a scalable and simple method for realizing thickness controllability is the key factor in fabricating atomically thin metal oxide films.…”
Section: Introductionmentioning
confidence: 99%